THE PHYSIOLOGICAL EFFECTS PLAYING BEACH HANDBALL HAS ON JUNIOR HANDBALL INDOOR PLAYERS - Paul Ovidiu RADU; Maria Daniela MACRA-OȘORHEAN; Rodica Cristina PETRUȘ; Vlad Alexandru TOMA (Cluj University Press, 2022)
Beach handball is a branch of sports that was born on the beaches of Italy in the early 1990s and it was designed to help players under go their physical training in a more dynamic training during the summer. Objectives. The main goal of this study is to describe the physiological state of the athletes that underwent a series of beach handball training sessions and to determine the effects of such training sessions on junior level beach handball athletes. Materials and methods. We have suggested that the evaluation of the athletes' condition be determined via invasive methods, such as the analysis of their urinary value. Results. The numerical data obtained from our analysis were computed using Student's t-test for unpaired samples associated with Welch's unequal variance t-test. The statistical significance was determined for an associated P <0.05 (probability > 95%). The comparison was made between the mean of the initial values and the mean of the final value for all the dosed biochemical markers. The data are expressed as mean ± SD (standard deviation). The statistical processing was done using the GraphPad Prism software. Conclusions. Including beach handball practice sessions in the training program of indoor handball players has no significant effect on their physiological state. Article history: Received 2022 September 20; Revised 2022 September 27; Accepted 2022 September 28; Available online 2022 November 20; Available print 2022 December 20. REZUMAT. Efectele practicării jocului de Beach Handball la nivel fiziologic asupra jucătorilor de handbal junior. Jocul de Beach Handball este o ramură sportivă nouă care a luat naștere pe plajele din Italia la începutul anilor 1990 cu intenția de a face pregătirea fizică a jucătorilor de handbal mult mai dinamică pe perioada verii. Obiective. Obiectivul principal al studiului a fost conturarea statusului fiziologic al sportivilor supuși unor serii de antrenamente organizate de Beach Handball și determinarea efectelor fiziologice în urma aplicării jocului de Beach Handball în pregătirea jucătorilor de handbal la nivel de juniori. Materiale și metode. Am propus evaluare stării sportivilor prin metode invazive, cum ar fi determinarea valorii unitare a acestora. Rezultate. Datele numerice obținute în urma determinărilor efectuate au fost prelucrate cu testul t Student pentru valori neperechi asociat cu corecția lui Welch. Semnificația statistică a fost stabilită la un P asociat < 0.05 (probabilitate > 95%). Comparația s-a efectuat între media valorilor inițiale și media valorilor finale, pentru toți markerii biochimici dozați. Datele sunt exprimate ca medie ± ES (eroarea standard a mediei). Prelucrarea statistică a datelor s-a efectuat folosind softul GraphPad Prism 5. Concluzii. Introducerea antrenamentelor de Beach Handball în programul de pregătire al jucătoarelor de handbal (indoor) nu influențează statusul fiziologic a acestora. Cuvinte cheie: handbal pe plajă, juniori, stare fiziologică.